(cosA - sin A + 1)/(cosA + sinA - 1)

Divide numerator and denominator by sinA, we get

=(cosA/sinA - sinA/sinA + 1/sinA)/ (cosA/sinA + sinA/sinA - 1/sinA)

=(cotA - 1 + cosecA)/(cotA+1- cosecA)

= (cotA + cosecA- 1)/cotA + 1 - cosecA)

We know that cosec

so we replace 1 by cosec

=[cotA + cosecA - (cosec

=[(cotA + cosecA)- (cosecA - cotA)(cosecA+cotA)]/(cotA -cosecA + 1)

taking cosecA + cotA common, we get

=cosecA + cotA[1-(cosecA - cotA)]/(cotA - cosecA + 1)

=cosecA + cotA(1-cosecA + cotA)/(cotA - cosecA +1)

=cosecA + cotA Proved {1-cosecA + cotA cancelled out}

Divide numerator and denominator by sinA, we get

=(cosA/sinA - sinA/sinA + 1/sinA)/ (cosA/sinA + sinA/sinA - 1/sinA)

=(cotA - 1 + cosecA)/(cotA+1- cosecA)

= (cotA + cosecA- 1)/cotA + 1 - cosecA)

We know that cosec

^{2}A - cot^{2}A= 1so we replace 1 by cosec

^{2}A - cot^{2}A, we get=[cotA + cosecA - (cosec

^{2}A - cot^{2}A)]/(cotA - cosecA + 1)=[(cotA + cosecA)- (cosecA - cotA)(cosecA+cotA)]/(cotA -cosecA + 1)

taking cosecA + cotA common, we get

=cosecA + cotA[1-(cosecA - cotA)]/(cotA - cosecA + 1)

=cosecA + cotA(1-cosecA + cotA)/(cotA - cosecA +1)

=cosecA + cotA Proved {1-cosecA + cotA cancelled out}

- 67